Steps towards operationalizing One Health approaches. - Pepin KM; Carlisle K; Anderson D; Baker MG; Chipman RB; Benschop J; French NP; Greenhalgh S; McDougall S; Muellner P; Murphy E; O'Neale DRJ; et al. (Elsevier B.V., 2024)
One Health recognizes the health of humans, agriculture, wildlife, and the environment are interrelated. The concept has been embraced by international health and environmental authorities such as WHO, WOAH, FAO, and UNEP, but One Health approaches have been more practiced by researchers than national or international authorities. To identify priorities for operationalizing One Health beyond research contexts, we conducted 41 semi-structured interviews with professionals across One Health sectors (public health, environment, agriculture, wildlife) and institutional contexts, who focus on national-scale and international applications. We identify important challenges, solutions, and priorities for delivering the One Health agenda through government action. Participants said One Health has made progress with motivating stakeholders to attempt One Health approaches, but achieving implementation needs more guidance (action plans for how to leverage or change current government infrastructure to accommodate cross-sector policy and strategic mission planning) and facilitation (behavioral change, dedicated personnel, new training model).
Keywords: Domestic animals; Environment; Human health; One health implementation; Policy; Science-policy interface; Semi-structured interviews; Sustainable Development Goals; Wildlife